The role of inspiratory capacity and tidal flow in diagnosing exercise ventilatory limitation in Cystic Fibrosis. (February 2022) - Reuveny, Ronen; Vilozni, Daphna; Dagan, Adi; Ashkenazi, Moshe; Velner, Ariela; Segel, Michael J.
Abstract: Background: Exercise ventilatory limitation conventionally defined by reduced breathing reserve (BR) may underestimate the effect of lung disease on exercise capacity in patients with mild to moderate obstructive lung diseases. Objective: To investigate whether ventilatory limitation may be present despite a normal BR in Cystic Fibrosis (CF). Methods: Twenty adult CF patients (age 16-58y) with a wide range of pulmonary obstruction severity completed a symptom-limited incremental exercise test on a cycle ergometer. Operating lung volumes were derived from inspiratory capacity (IC) measurement during exercise and exercise tidal flow volume loop analysis. Results: six patients had a severe airway obstruction (FEV1 <45% predicted) and conventional evidence of ventilatory limitation (low BR). Fourteen patients had mild to moderate-severe airway obstructive (FEV1 46–103% predicted), and a normal BR [12–62 L/min, BR% (17–40)]. However, dynamic respiratory mechanics demonstrated that even CF patients with mild to moderate-severe lung disease had clear evidence of ventilatory limitation during exercise. IC was decreased by (median) 580 ml (range 90–1180 ml) during exercise, indicating dynamic hyperinflation. Inspiratory reserve volume at peak exercise was 445 ml (241–1350 ml) indicating mechanical constraint on the respiratory system. The exercise tidal flow met or exceeded the expiratory boundary of the maximal flow volume loop over 72% of the expiratory volume (range 40–90%), indicating expiratory flow limitation. Conclusion: Reduced BR as a sole criterion underestimates ventilatory limitation during exercise in mild to moderate-severe CF patients. Assessment of dynamic respiratory mechanics during exercise revealed ventilatory limitation, present even in patients with mild obstruction. Highlights: Breathing reserve may underestimates ventilatory limitation in mild to moderate-severe CF. Mild to moderate-sevcere CF have abnormal respiratory mechanics despite of normal BR. Assessment of dynamic respiratory mechanics during exercise is necessary in CF. In severe CF patients, ventilatory limitation can be detected by reduced BR.